Psychological service of the university: a range of problems and directions of development - G. A. Velichko; G. Yu. Lizunova; I. A. Taskina (Вестник университета)
The article considers the topical and important issue of modern higher education: problems and development of psychological services at the university. The practice of working as psychologists-consultants at the university shows the current need to discuss this issue. Students who have come from schools and colleges are used to seeing psychologists among their “helpers” to solve psychological problems, problems in communicating with peers and teachers. In addition, the students, especially undergraduates, being experiencing the impact of the environment, need support from the psychological service. The authors substantiate the need for further development of the psychological service of a higher educational institution, identify a range of problems relevant to the psychological services of universities. The functional purpose of the psychological service of the university is determined. Its purpose and objectives are indicated, and proposals on ways to improve the organisation development of psychological services in higher educational institutions are given.